Decentralization and party politics in the dominican republic - Mitchell, Christopher; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
Recently in the Dominican Republic, a pro-municipal social alliance pressed for decentralization and politicians yielded, seeking power in three-party competition. This study examines how electoral, financial, and administrative power has been dispersed and suggests innovative strategies to maintain decentralizing momentum.
Keywords: Culture -- Study and teaching; Ethnology -- Latin America; Political science; Comparative politics; Democracy; Latin America -- Politics and government; Cultural and Media Studies; Latin American Culture; Latin American Politics; Comparative Politics; Democracy; Political Science